An inquiry into the guidelines on the application of EU competition law to collective agreements concerning the working conditions of the solo self-employed - Giampa, Gianluca (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
The purpose of this article is to examine the compatibility of collective agreements for self-employed persons with the principles of European competition law. According to European law, self-employed persons are considered to be on equal footing with companies, thus making them susceptible to violating competition rules by entering into agreements on working conditions. The judgments of the European Court of Justice in the Albany and FNV Kunsten cases have established that collective agreements for self-employed persons are not generally exempted from the rules prohibiting restrictions on competition. However, considering the protection needs of numerous self-employed persons, a change in approach seems necessary. In 2022, the European Commission adopted Guidelines aiming to clarify the scope of EU competition law regarding col- lective agreements for self-employed persons. The objective is to exclude self-employed individuals who are most in need of trade union protection. However, there are some critical points in the Guidelines that warrant attention, such as the assessment of the compatibility of collective agreements for self-employed persons with competition law being conducted on an individual basis. A collective approach to the issue appears nec- essary instead of an individual one. Therefore, it seems appropriate to reflect on the dialectic between market freedom and social rights in European law concerning this specific issue, particularly in light of the recent proposal.
Keywords: delovne pogodbe; Evropska unija; evropsko delavno pravo; evropsko konkurenčno pravo; kolektivne pogodbe; pravice delavcev; samozaposleni; samozaposlovanje; socialne pravice; svoboda trga